Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-24980-x_24
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence the Acrylamide Content of Heated Foods

Abstract: Our finding that acrylamide is formed during heating of food initiated a range of studies on the formation of acrylamide. The present paper summarizes our follow-up studies on the characterization of parameters that influence the formation and degradation of acrylamide in heated foods. The system designed and used for studies of the influence of added factors was primarily homogenized potato heated in an oven. The net content of acrylamide after heating was examined with regard to the following parameters: hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 14 publications
8
34
0
Order By: Relevance
“…Rydberg et al (2005) reported that the higher temperature (200 C) combined with prolonged heating led to reduced levels of acrylamide, due to elimination/ degradation processes. Increased protease activity of LAB may result in an enhanced release of amino acids from proteins.…”
Section: Effect Of Lactofermentation On Acrylamide Contentmentioning
confidence: 98%
See 3 more Smart Citations
“…Rydberg et al (2005) reported that the higher temperature (200 C) combined with prolonged heating led to reduced levels of acrylamide, due to elimination/ degradation processes. Increased protease activity of LAB may result in an enhanced release of amino acids from proteins.…”
Section: Effect Of Lactofermentation On Acrylamide Contentmentioning
confidence: 98%
“…In particular, L. sakei and spontaneous fermentation decreased the pH by 35.9% at the end of fermentation; while the Pedioccocus strains were found to be weaker acidifiers decreasing the pH by 32.2%. Rydberg et al (2005) reported that the pH-dependence of acrylamide formation exhibited a maximum of around pH 8; a lower pH enhanced the elimination and deceleration of acrylamide. Addition of a protein-rich food component reduces the acrylamide content probably by promoting competing reactions and/or covalently binding of formed acrylamide (Rydberg et al, 2005).…”
Section: Effect Of Lactofermentation On Acrylamide Contentmentioning
confidence: 98%
See 2 more Smart Citations
“…Acrylamide formation is affected by many factors, such as precursors (i.e., reducing sugar and asparagine) concentration, pH, water content and activity, physical state of the food, and process parameters, mainly represented by the heating time and temperature [12, 28,48,57,60,62,69,70,77]. For instance, acrylamide formation is favored by a high heating temperature and time, as well as pH values, a relatively low water content and activity.…”
Section: Introductionmentioning
confidence: 99%